METODE BELAJAR ONLINE TERHADAP TINGKAT KECERDASAN ANAK SD ERA PADEMI COVID-19 - Syafitri, Lili; Asmawati; Hendarmin, Rum; Hartati, Lesi (Transpublika Publisher, 2021)
In online learning, the teaching and learning process is facilitated by the use of the internet and digital media to convey the material. Online learning is believed to be more aligned with the current generation of students, who are well-known for their high level of integration with technology products. This is a form of digitization in the field of education that provides a number of advantages. From a practical standpoint, the benefits of online learning in the Covid-19 pandemic era include the ability for teachers and students to interact more effectively because they will not have to physically meet. Additionally, there is no classroom for formal education. The teaching and learning process can occur anyplace as long as the environment is conducive and can aid in concentration. Furthermore, there is no requirement to